PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP DISIPLIN KERJA DENGAN MEDIASI MOTIVASI KERJA PADA PEGAWAI DISPORABUDPAR GROBOGAN - Khomariyah, Nurul; Saddewisasi, Wyati; Sugiarti, Rini (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aims to determine the influence of leadership style and organizational culture on work discipline, with work motivation role as an intervening variable among employees of the Disporabudpar office in Grobogan Regency. The independent variables in this research are leadership style and organizational culture. The dependent variable is work discipline, with work motivation acting as a mediating variable. This research used a quantitative method with a questionnaire as the instrument. The sample in this research consisted of 76 employees selected using the census method. The analysis was structural equation modeling (SEM) using the SmartPLS analysis tool. The results of this research show that leadership style and organizational culture have a significant positive effect on work motivation. Motivation has a positive and significant effect on work discipline, and leadership style and organizational culture have been proven to have a positive and significant effect on work discipline. The motivation variable mediate the relationship between leadership style and organizational culture on work discipline. Keywords: Discipline; Motivation; Leadership Style; Organizational Culture